Recent Progress of Multifunctional Silica Aerogel Composite Materials: From Fabrication Strategies to Versatile Applications - Li, Yang; Peng, Li-Dong; Bao, Dun-Peng; Zhu, Guo-Tao; Ma, Lin; Chen, Zuan-Yu; Cao, Cheng-Fei; Liu, Shuai-Chi; Yang, Fan; Zhang, Guo-Dong; Gao, Jie-Feng; Bae, Joonho; et al. (ACS applied materials & interfaces, 2025)
Silica aerogels are considered promising materials for use in harsh environmental conditions due to their low density, high specific surface area, high porosity, and low thermal conductivity. However, traditional silica aerogels face some obstacles to widespread practical applications due to insufficient mechanical robustness, environmental stability, and limited functionalization. The addition of functional fillers and polymer materials is an effective method to enhance the physical properties and multiple functionalities of silica aerogels. This review aims to summarize recent progress in the fabrication, properties, and applications of silica aerogel composites. Various methods and components used to modify silica aerogels, including fibers, carbon, and polymer materials, are summarized and introduced, followed by a description of their multifunctional applications in thermal management, ablation resistance, oil/water separation, and more. Finally, the perspectives and future research directions in the development of advanced silica aerogel composites are also discussed and highlighted.